KOMPARASI IKON CABANG OLAH RAGA ASIAN GAMES 2018 JAKARTA-PALEMBANG DAN ASIAN PARA GAMES 2018 - Ika Resmika Andelina (Universitas Mercu Buana, 2019)
Along with the development of technology and the world economy, the use of icons is often found in the creative industries. Icon application can be of various uses, ranging from application icons for devices, sign systems, software, road markings, and others. According to Van Leeuwen, iconography means